Analisis Pengaruh Lingkungan Kerja, Kepemimpinan Dan Disiplin Kerja Terhadap Kinerja Karyawan Perusahaan Konstruksi Pada Pembangunan Terminal Selatan Bandar Udara Internasional Sultan Hasanuddin Makassar - Puspitasari, Hilda; Mulyani, Savitri Prasandi; Setiawan, Arman (Program Studi Teknik Sipil Universitas Bosowa, 2025)
The low performance ethos displayed by employees of the Sultan Hassandin Makassar International Airport Development Project is of course related to the leadership implemented by the leader. Because leadership is an activity that influences and directs the behavior of subordinates or other people to achieve organizational or group goals. Apart from that, the work environment at the Sultan Hassandin Makassar International Airport Development Project is not good, there are still employees who appear relaxed during working hours, and there are also employees who chat with colleagues during working hours. Moreover, work discipline at the Sultan Hassandin Makassar International Airport Project Construction which is not conducive to work discipline can cause employee performance to be less than optimal. The quality of the work environment, work discipline and leadership of construction companies can have a significant and positive influence on employee performance at the Bandar Sultan Hasanuddin Makassar Development Project with an influence value on work environment variables of 0.483, leadership variables of 0.352, and work discipline of 0.454. Where in this research the work environment variable is the variable that has the greatest influence on employee performance in the construction of the southern terminal of Sultan Hasanuddin Makassar International Airport.